2018
DOI: 10.1590/s1677-5538.ibju.2016.0611
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and durability of solifenacin versus percutaneous tibial nerve stimulation versus their combination for the treatment of women with overactive bladder syndrome: a randomized controlled study with a follow-up of ten months

Abstract: PurposeTo assess effectiveness and durability of Solifenacin (SS) versus tibial nerve stimulation (PTNS) versus combination therapy (PTNS + SS) in women with overactive bladder syndrome (OAB).Materials and Methods105 women with OAB were divided randomly into three groups of 35 patients each. In group A women received SS, in group B women underwent PTNS, in group C women underwent combination of PTNS + SS. Improvements in OAB symptoms were assessed with OABSS questionnaire; patients’ quality of life was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The largest study with 105 women with OAB compared solifenacin alone with PTNS alone with solifenacin and PTNS combined [14]. Results demonstrated that PTNS was more effective than solifenacin, but that combination therapy was the most effective and demonstrated more durability than PTNS and solifenacin alone.…”
Section: Ptns and Anti-muscarinic Treatmentmentioning
confidence: 99%
“…The largest study with 105 women with OAB compared solifenacin alone with PTNS alone with solifenacin and PTNS combined [14]. Results demonstrated that PTNS was more effective than solifenacin, but that combination therapy was the most effective and demonstrated more durability than PTNS and solifenacin alone.…”
Section: Ptns and Anti-muscarinic Treatmentmentioning
confidence: 99%
“…Four prospective studies have evaluated percutaneous tibial nerve stimulation (PTNS) in combination with anticholinergic medications (either tolterodine or solifenacin; Table ) . All four studies include fewer than 40 patients, though universally report that combination therapy improves urinary frequency, urgency, and urge incontinence outcomes compared to either anticholinergic monotherapy or PTNS monotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Four prospective studies have evaluated percutaneous tibial nerve stimulation (PTNS) in combination with anticholinergic medications (either tolterodine or solifenacin; Table 3). [32][33][34][35] All four studies include fewer than 40…”
Section: Posterior Tibial Nerve Stimulation With Medicationsmentioning
confidence: 99%
“…They found no statistical differences between solifenacin and PTNS group in terms of daily and night time micturiction frequency, urgency, urgency incontinence, and quality of life; on the contrary, they found a significant difference between the combination therapy group and the other two in all aforementioned domains (all p < 0.05). 32…”
Section: Ptnsmentioning
confidence: 99%
“…They found no statistical differences between solifenacin and PTNS group in terms of daily and night time micturiction frequency, urgency, urgency incontinence, and quality of life; on the contrary, they found a significant difference between the combination therapy group and the other two in all aforementioned domains (all p < 0.05). 32 In a large prospective cohort of 200 patients, Del Río-Gonzales et al evaluated the durability of PTNS. They demonstrated the efficacy of PTNS with a success rate of 73.5% and a symptom improvement in 20.5%; 90.5% of patients reached a clinical improvement >50%.…”
Section: Ptnsmentioning
confidence: 99%